Sistem Informasi Pengelolaan Piutang Dan Pembelian Hasil Nilam (Pogostemon Cablin) Pada Kelompok Tani Potoutusan Desa Ampera - Supriyadi La Wungo; Trisno Wibowo K; Yadda Undeng (Journal of System and Computer Engineering (JSCE), 2022)
The purpose of this research is to design and build an information system that can help the Young Farmers Group Of Ampera Village, Pagimana District, Banggai Regency in managing the receivables of its members and the purchase of patchouli crops from farmers and existing members. As we know together today the Nilam plant (Pogostemon Cablin) becomes the prima donna of agriculture because of the relatively short planting time (4-6 months) and commodity prices are quite high in the market. This research uses the concept of qualitative methods with several data collection techniques such as interviews, literature studies, and direct observation. While in the implementation of the system using context diagram tools, diagram zero, data flow diagram, and ERD integrated with MySql database. The results of this study show that the information system designed and built can solve the problems that exist in the Young Farmers Group working related to the management of receivables and purchase transactions from non-member members and farmers, this information system can also present data/information quickly and efficiently.